Lean construction in crisis times: responding to the post-pandemic AEC industry challenges - Alarcón, Luis F.; González, Vicente A. (Pontificia Universidad Católica del Perú. Facultad de Arte y Diseño, 2021)
While our IGLC community was trying to catch up with how the reshaping of the manufacturing by the advent of the “fourth industrial revolution” or industry 4.0 would impact the architecture-engineering-construction (AEC) industry, an even bigger and unprecedented economic and social disruption caused by the outbreak of the COVID-19 pandemic in 2020, posed new and unimaginable challenges leading to a world that is going through its biggest transformation in every single aspect of our society in almost a Century. Countries responded to the COVID-19 pandemic by taking unprecedented steps such as making large amounts of money available to fund rescue measures such as tax cuts, extended unemployment benefits, mortgage holidays, and liquidity for small and medium-sized businesses. And some of the millions of persons that suddenly started working remotely during the pandemic, have taken the unprecedented opportunity to shift their lives in a new direction expecting not having to go back to the office again. This has also shifted the traditional way of working in the AEC industry towards one that enable the e-office and e-collaboration among project teams. Back in 2020, the 28th IGLC conference already setup (i.e., auditoriums, catering, hotel reservations, audiovisual equipment) to be carried out in Cusco, Peru had to be surprisingly cancelled due to the COVID-19 worldwide lockdown and traveling restrictions imposed throughout the word in March 2020. Iris Tommelein1 and her P2SL group at UC Berkeley jointly with Emmanuel Danie2 from University of Wolverhampton, raised to the occasion making the IGLC community statement “annual conferences are the main activity of the IGLC, and their locations rotate amongst the continents” to become charged with a new meaning, having by the first time a completely online IGLC conference in 2020. The 28th IGLC online conference organized by the P2SL at Berkeley replaced the originally planned in person conference to be held in Cusco, Peru in July 2020. Building on top of the pioneering experience provided by UC Berkeley, this year’s 29th IGLC full online conference has been entirely organized by the Peruvian university: “Pontificia Universidad Católica del Perú” under the leadership of Professors Dr Danny Murguia and Dr Xavier Brioso, and with the senior advice of Professors Dr Luis Fernando Alarcon from Catholic University of Chile and Dr Vicente Gonzalez from University of Auckland. In this year’s conference, we had 98 papers’ presentations, 9 Summer School presentations, 2 keynote speakers, and a Gregory Howell Lean Game Session. All the papers and presentation slides are available online at iglc.net. With the conviction that we shall emerge from this COVID-19 pandemic with a healthier respect for the environment and our common humanity, Dr Flores inaugurated the conference with the keynote presentation: “Trust, emotionality, relationships, and productivity - some reflections for the construction industry”. And Dr Guilherme Luz Tortorella provided the closing keynote presentation “Integrating Industry 4.0 into Lean”. These IGLC29 conference proceedings do not only contain the records of the conference, but they will carry within themselves the story of the challenges and opportunities brought up by the COVID-19 pandemic to our IGLC community as well as to the broader Lean Construction community. Finally, we would like to thank to all the members of the 2020 28th IGLC conference organizing committee that was not possible to be carried out in person in Cusco, Peru neither during 2020 nor during 2021, special thanks to Carlos Lepesqueur for his efforts and leadership on the organization of a conference that did not happen and that we still hope to happen in the new world of hope that has started to arise.
Keywords: Lean construction; https://purl.org/pe-repo/ocde/ford#2.01.01